1996
DOI: 10.1038/bjc.1996.451
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E overexpression, a negative prognostic factor in breast cancer with strong correlation to oestrogen receptor status

Abstract: Summary Cyclin E is a GI cyclin which has been proposed to be one of the key regulators of the important GI/S transition, and could consequently be a potential deregulated molecule in tumours. Recently, it has been observed that cyclin E is overexpressed in a variety of malignancies including breast cancer and that several isoforms of the protein exists. In this study we have characterised the cyclin E expression in 114 tumour specimens from patients with primary breast cancer using Western blotting. Various e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
158
3

Year Published

1997
1997
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(175 citation statements)
references
References 29 publications
14
158
3
Order By: Relevance
“…The overexpression of cyclin E may result from a synergy between TGFa and cMyc, because expression of cyclin E is not pronounced in the hyperplastic epithelium from either tgfa or c-myc animals. This hypothesis is consistent with the observation in human breast cancer, that overexpression of cyclin E is correlated with increased tumor grade (Nielsen et al, 1996;Keyomarsi, et al, 1994). Moreover, a well-known, but mechanistically-unclear phenomenon is that overexpression of the c-myc gene alone is insu cient for transformation of most types of cells either in vitro or in vivo; cooperation of c-myc with growth factors (like TGFa) or some oncogenes (such as .…”
Section: Discussionsupporting
confidence: 91%
“…The overexpression of cyclin E may result from a synergy between TGFa and cMyc, because expression of cyclin E is not pronounced in the hyperplastic epithelium from either tgfa or c-myc animals. This hypothesis is consistent with the observation in human breast cancer, that overexpression of cyclin E is correlated with increased tumor grade (Nielsen et al, 1996;Keyomarsi, et al, 1994). Moreover, a well-known, but mechanistically-unclear phenomenon is that overexpression of the c-myc gene alone is insu cient for transformation of most types of cells either in vitro or in vivo; cooperation of c-myc with growth factors (like TGFa) or some oncogenes (such as .…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of cyclin E expression may be underestimated in studies utilizing Western blotting techniques, because of the heterogeneity and presence of non-cancerous cells in the sample and varied amounts of extracellular stromal proteins. However, the percentage of carcinomas considered to have greater reactivity was very similar to that found by Nielsen et al (1996).…”
Section: Evaluation Carcinomassupporting
confidence: 74%
“…Overexpression of cyclin E has been observed in 10 out of 10 breast cancer cell lines and breast tissue using Western blotting techniques (Keyomarsi and Pardee, 1993;Keyomarsi et al, 1994;Nielsen et al, 1996). It has been suggested that deregulation of cyclin E may be a factor contributing to the malignant phenotype (Keyomarsi and Pardee, 1993;Keyomarsi et al, 1994;Dutta et al, 1995).…”
Section: Evaluation Carcinomasmentioning
confidence: 99%
See 2 more Smart Citations